2007
DOI: 10.3989/mc.2008.v58.i289-290.71
|View full text |Cite
|
Sign up to set email alerts
|

Biorreceptividad de las dolomías a la colonización fúngica

Abstract: RESUMENEn este trabajo se evalúa cómo influye la textura de las dolomías en las estrategias adoptadas por los microorganismos para colonizar estos materiales pétreos. Para ello se han caracterizado muestras de dolomías con diferentes texturas mediante microscopía electrónica de barrido en modo de electrones retrodispersados (SEM-BSE), microscopía electrónica de barrido a bajas temperaturas (LTSEM), microscopía de luz transmitida (TLM) y porosimetría por intrusión de mercurio (MIP). De estas observaciones se de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…The inoculation of marble samples with fungi has shown that they are able to penetrate the substrate actively and produce pits. Camara et al [65], studying fungal colonization on three dolostones from monuments and natural outcrops, confirmed that the intercrystalline penetration was the initial stage of stone fungi interactions, followed by intracrystalline penetration and finally the complete disaggregation of the crystals. The different stages of interactions with the dolostones depend on the extent and type of porosity.…”
Section: Fungimentioning
confidence: 88%
“…The inoculation of marble samples with fungi has shown that they are able to penetrate the substrate actively and produce pits. Camara et al [65], studying fungal colonization on three dolostones from monuments and natural outcrops, confirmed that the intercrystalline penetration was the initial stage of stone fungi interactions, followed by intracrystalline penetration and finally the complete disaggregation of the crystals. The different stages of interactions with the dolostones depend on the extent and type of porosity.…”
Section: Fungimentioning
confidence: 88%
“…Although Meslier et al (2018) suggested that the chemical properties of the rock may not be an essential driver of community composition and diversity, the ability of microorganisms to use nutrients leached from rocks can affect the community composition in their niche. In addition, Cámara et al (2008) suggested that the microstructure of the rock, such as the space available for colonization and its physical structure, linked to water retention capabilities, can be a determinant of the potential bioreceptivity of lithic habitat. In our study, despite the clearly different chemical composition and microhabitat architecture of limestone and sandstone, the structures of archaeal, bacterial, and protistan communities were similar in both limestone and sandstone, which is consistent with the previous studies on lithic communities from polar deserts (de la Torre et al, 2003;Pointing et al, 2007;Archer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…), on the yellow dolostone (mostly calcitic dolomite) of San Martín de Fuentidueña, originally located in Segovia, Spain, but now at the cloisters of the Metropolitan Museum of Art in New York (Figure 4). detected both epilithic and endolithic colonization by ascomycetous and basidiomycetous fungi, with green algae, cyanobacteria, and fungal-algal association, on dolostone samples from the Redueña quarry and also proposed that petrographic characteristics influenced endolithic growth (Cámara et al, 2008). In general, fungal filaments, hyphae, colonized existing pores, growing into the larger spaces regardless of whether they were inter-or intracrystalline.…”
Section: Figurementioning
confidence: 94%